Efeitos da estimulação transcraniana por corrente contínua no córtex pré-frontal em estratégias de regulação emocional em mulheres - Medeiros, Natany de Souza Batista (2021)
The Emotional Regulation (ER) strategies are cognitive processes that modify emotional experience, and their execution is associated with activation of the prefrontal cortex (PFC). Transcranial direct-current stimulation (tDCS) is a method that promotes changes in cortical excitability and has been used in the functional investigation of CPF. However, few studies have explored the effects of neuromodulation on ER strategies. The aim of this work was to investigate the effects of tDCS in different regions of the prefrontal cortex in ER. For this, three studies were carried out with the participation of women, aged between 18 and 35 years, without a history of neurological and psychiatric diseases, without the use of psychotropic medications. In the first study, the effect of tDCS was investigated on the right and left dorsolateral PFC on ER strategies (passive observation, distraction and revaluation) and on the inventive capacity for reappraisal. It was found that anodal tDCS in the right dorsolateral PFC reduced emotional arousal in the face of negative images regardless of the strategy used and a trend towards the effect of anodal tDCS on the left PFC on the number of reappraisals generated in the RIT. In the second study, the objective was to investigate the effect of anodal tDCS on the right ventrolateral PFC in the execution of RE strategies, using the same methodology as in study 1. It was found that the anodal tDCS on the right ventrolateral PFC increased the inventive capacity in reappraisal, and there was an effect of interaction between group and strategies on intensity responses. In the third study, we investigated the effect of anodal tDCS on left and right dorsolateral PFC and right ventrolateral PFC on the number of intrusive thoughts during mindfulness practice before and after worry induction and on self-reported perception of positive and negative emotions. It was found that tDCS in the left dorsolateral PFC decreased the amount of intrusive thoughts and caused higher scores of positive affect after the experiment. It is concluded that tDCS in different regions of the PFC has an effect on ER, with specificity of the effects depending on the target cortical region, the hemisphere and particularities in the conduct of the emotional task.